KADAR GLIAL FIBRILLARY ACIDIC PROTEIN SERUM TINGGI SEBAGAI FAKTOR RISIKO NYERI NEUROPATIK PADA KUSTA TIPE MULTIBASILER - Sofyan Faridi*, I Made Oka Adnyana*, I Putu Eka Widyadharma*, Luh Made Mas Rusyati** (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION LEPROSY IS ONE OF THE MOST COMMON CAUSES OF NONTRAUMATIC PERIPHERAL NEUROPATHY IN THE WORLD THERE ARE MANY FACTORS CAUSING NEUROPATHIC PAIN IN MULTIBACILLARY MB TYPE LEPROSY ONE OF WHICH IS AN INCREASE IN SERUM LEVELS OF GLIAL FIBRILLARY ACIDIC PROTEIN GFAP